The Experience of Female Nurses Working in the Emergency Room in Balancing Their Personal Lives With Their Work: A Phenomenological Study - Prita Laora, Naia; Suryani; Dedy Suprayogi (International Conference on Sustainable Health Promotion, 2025)
The nursing profession is inherently demanding, characterized by irregular working hours, high workload, and substantial responsibility, all of which can significantly impact nurses’ ability to maintain a healthy work-life balance. Female nurses working in emergency rooms face unique challenges due to the high-pressure nature of the work environment and their dual roles as healthcare providers and mothers. This study aims to explore the lived experiences of female ER nurses in managing and balancing their professional and personal responsibilities using a phenomenological approach. Data were collected through in-depth, semi-structured interviews with three nurses who have children under the age of 10, selected via purposive sampling. Thematic analysis revealed that the primary challenges include unpredictable work schedules, heavy workload, and emotional strain, which often result in fatigue and reduced quality time with family. Nevertheless, participants employed various coping strategies such as task prioritization, seeking social support, and implementing self-management techniques to effectively navigate these challenges. The findings underscore the importance of flexible work arrangements and supportive organizational environments in enhancing nurses’ work-life balance, thereby improving their overall well-being and professional performance.